(untitled) (PerCursos, 2022)
"Look at me again?" is an invitation that Linn da Quebrada makes to us when she launches her second album, "Trava Línguas" (2021), which consists of establishing possibilities of opening and another dialogue with her and with her art. Another look at her own existential and musical construction. Twenty years after the death of professor Milton Santos, this same invitation to a new look is made to students, researchers and professors, not only of geography, for another epistemological and corporal re-elaboration of Milton Santos. The consolidation of an epistemology of existence, which is fundamentally dialogic, and which envisages the investigation of action in everyday life, understood by the author as a continuous space, facilitates, based on the work of Milton Santos, the analysis of the issues read by the existential perspective and by the relational sense of the body with space, through corporeality. The dialogicity between geography and art, having Linn da Quebrada as an artistic and political reference, beyond the initial question, is carried out by her creativity, inventiveness and active organic intellectuality, which tension the spatial understandings, exploring a deep existence, revealing a body - plural spatiality. It is, therefore, a reconstruction of the method through life, in which the embodied geography is made – on a daily basis – in the gaps in the closed web of science.